STUDI KLOROFIL-a DI KAWASAN PERAIRAN BELAWAN SUMATERA UTARA Study of chlorophyll-a around sea of Belawan, North Sumatera - Amanda Paramitha; Budi Utomo; Desrita Desrita (AQUACOASTMARINE, 2014)
There many activities around marine Belawan alters the marine water quality of Belawan. The information and understanding of environmental change are indispensable in ecosystem monitoring efforts. This research aims for knowing the study of chlorophyl-a, and the relationship between physical and chemical factors was done on Desember 2013 – February 2014 in sea of Belawan, North Sumatera. The sampling was determined based on four location which is in various activities. There are 4 sampling in 3 months. The analysis of other factor, such as water temperature, pH, brightness, salinity, DO, nitrate, phosphate, and chlorophyll. The result of research showed there was a relation of physical chemical factors in sea of Belawan, North Sumatera. The range of the chlorophyll-a is 1,93 – 5,96 mg/ m3. The highest concentration of chlorophyll-a was located in floating net cages in the range of 4,06 – 5,96 mg/m3. The lowest concentration of chlorophyll-a was located in offshore in the range of 1,93 – 2,53 mg/m3. The average value chlorophyll top are on the location 4 and the lowest in the location.Keywords : Chlorophyll-a, sea of Belawan